2017
DOI: 10.1016/j.ymgme.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase haploinsufficiency in A53T α-synuclein mice impacts disease onset and course

Abstract: Mutations in GBA1 encountered in Gaucher disease are a leading risk factor for Parkinson disease and associated Lewy body disorders. Many GBA1 mutation carriers, especially those with severe or null GBA1 alleles, have earlier and more progressive parkinsonism. To model the effect of partial glucocerebrosidase deficiency on neurological progression in vivo, mice with a human A53T α-synuclein (SNCAA53T) transgene were crossed with heterozygous null gba mice (gba+/−). Survival analysis of 84 mice showed that in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 45 publications
5
30
2
Order By: Relevance
“…Accumulation of GlcCer and lower levels of LacCer in the DRGs suggest that the lysosomal metabolism of GlcCer via glucocerebrosides (GBA1) to LacCer is impaired, which would agree with associations of GBA1 dysfunctions with PD [28], and with increased alpha synuclein toxicity in the presence of GBA1 mutations [27,29,47]. Gene expression analysis (RNAseq) in the DRGs of our mice did not reveal lower GBA1 transcription (Suppl.…”
Section: Accumulation Of Glucosylceramides In Drgs and Loss Of Sphingsupporting
confidence: 77%
See 1 more Smart Citation
“…Accumulation of GlcCer and lower levels of LacCer in the DRGs suggest that the lysosomal metabolism of GlcCer via glucocerebrosides (GBA1) to LacCer is impaired, which would agree with associations of GBA1 dysfunctions with PD [28], and with increased alpha synuclein toxicity in the presence of GBA1 mutations [27,29,47]. Gene expression analysis (RNAseq) in the DRGs of our mice did not reveal lower GBA1 transcription (Suppl.…”
Section: Accumulation Of Glucosylceramides In Drgs and Loss Of Sphingsupporting
confidence: 77%
“…In addition, it has been recognized in recent years that metabolic deregulations of bioactive lipids including ceramides and their metabolites increase the toxicity of alpha-synuclein [25][26][27]. Patients who are heterozygous carriers of glucocerebrosidase (GBA1) mutations tend to develop a rapidly progressive disease [28], and such mutations propagate alpha synuclein deposition in PD model organisms [29][30][31][32]. GBA1 is a lysosomal enzyme that catalyzes the degradation of ceramides to glucosylceramides (GlcCer) and subsequent generation of lactosylceramides (LacCer) and gangliosides.…”
mentioning
confidence: 99%
“…The hypothesis that GBA1 could affect α-synuclein degradation and pathology has been tested in several animal models [ 8 , 10 , 30 , 37 , 44 ]. These models have allowed us to elucidate the relationship among GBA1, α-synuclein, and PD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the early-onset PD was identified in the patients with low GBA1 enzyme activity through an imaging study [ 21 ]. Several studies attempted to define the effect of GBA1 deficiency on α-synuclein accumulation, turn over and its consequent pathology in vivo [ 8 , 10 , 30 , 37 , 44 ]. Although the studies have partially relationship among GBA1, α-synuclein, and PD, the animal models fail to represent GBA1-associated Parkinsonism, lacking an earlier age of PD onset and dopaminergic neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…While it is generally believed that in autosomal recessive diseases the heterozygotes are phenotypically normal, it is increasingly evident that haploinsufficiency of a gene product may lead to phenotypic manifestations that are different from that of the complete absence of the same gene product. For example, while the complete deficiency of β‐GBA causes type‐2 Gaucher's disease, haploinsufficiency of β‐GBA may manifest as Parkinson's disease in humans and in mice . Moreover, it has been reported that while complete ablation of the CLN11 gene encoding progranulin causes NCL11‐disease in humans and in mice, its haploinsufficiency manifests as frontotemporal dementia .…”
Section: Discussionmentioning
confidence: 99%